Adam Smith, Settler Colonialism, and Limits of Liberal Anti-Imperialism - INCE, Onur Ulas (Institutional Knowledge at Singapore Management University, 2021)
Recent scholarship has claimed Adam Smith's frontal attack on the mercantile system as a precocious expression of liberal anti-imperialism. This paper argues that settler colonialism in North America represented an important exception and limit to Smith’s anti-imperial commitments. Smith spared agrarian settler colonies from his invective against other imperial practices like chattel slavery and trade monopolies because of the colonies’ evidentiary significance for his “system of natural liberty.” Smith’s embrace of settler colonies involved him in an ideological conundrum insofar as the prosperity of these settlements rested on imperial expansion and seizure of land from the indigenous peoples. Smith navigated this problem by, first, predicating colonial “injustice” on conquest, slavery, and destruction, and second, describing American land as res nullius. Together, these conceptual definitions made it possible to imagine settler colonies as originating in nonviolent acts of “occupation without conquest” and embodying “commerce without empire.”